La penitencia: el verdadero camino hacia la paz1 (2019)
Peace is an enormous value for society. History teaches us that it is not easy to achieve. A change is needed to carry out this project of peace. In this article it starts with the idea that this change must begin in the same person so that it can extend to the whole society. We recognize this change in what is called in the Christian tradition penance. This change means a process and includes recognition of being a sinner, sincere confrontation with guilt, and willingness to accept spiritual therapy or spiritual medicine. A person cannot be healed by himself but needs divine grace